2020
DOI: 10.1007/s10529-020-02995-x
|View full text |Cite
|
Sign up to set email alerts
|

A plant-based transient expression system for the rapid production of highly immunogenic Hepatitis E virus-like particles

Abstract: Objective Hepatitis E virus (HEV) infection is a major cause of acute hepatitis worldwide. The aim of the study is the development of plant expression system for the production of virus-like particles formed by HEV capsid and the characterization of their immunogenicity. Results Open reading frame (ORF) 2 encodes the viral capsid protein and possesses candidate for vaccine production. In this study, we used truncated genotype 3 HEV ORF 2 consisting of aa residues 110 to 610. The recombinant protein was express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Here, we developed and optimized an HEV iEIA for the detection of serum IgG, based on the recombinant HEV-3 ORF2 110-610_6his capsid protein produced in N. benthamiana plants. Our previous studies describe the successful expression of the HEV-3 ORF2 110-610 gene [ 37 , 48 ] using the Cowpea Mosaic Virus (CPMV)-based vector pEAQ-HT [Sainsbury 2008 and 2009] and the potato X virus (PVX)-based vector pEff [ 41 ]. The latter showed higher HEV-3 ORF2 110-610_6his protein accumulation levels as compared to the CPMV-based vector pEAQ-HT [ 37 ], with a yield up to ~200 µg/g of fresh weight (FW) plants leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we developed and optimized an HEV iEIA for the detection of serum IgG, based on the recombinant HEV-3 ORF2 110-610_6his capsid protein produced in N. benthamiana plants. Our previous studies describe the successful expression of the HEV-3 ORF2 110-610 gene [ 37 , 48 ] using the Cowpea Mosaic Virus (CPMV)-based vector pEAQ-HT [Sainsbury 2008 and 2009] and the potato X virus (PVX)-based vector pEff [ 41 ]. The latter showed higher HEV-3 ORF2 110-610_6his protein accumulation levels as compared to the CPMV-based vector pEAQ-HT [ 37 ], with a yield up to ~200 µg/g of fresh weight (FW) plants leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the recombinant HEV-3 ORF2 110-610_6his was transiently expressed and characterized in plants, showing its immunogenic [ 48 ] and diagnostic potential [ 15 ]. In this study, we developed and optimized an in-house EIA designed to detect HEV serum antibodies in pigs, using the plant-derived HEV-3 ORF2 110-610_6his recombinant protein.…”
Section: Introductionmentioning
confidence: 99%
“…Our new system can be an alternative approach to widely used Agrobacterium- mediated transient gene expression. Agroinfiltration is the main approach used for the insertion of expression vectors in the plants to produce the recombinant proteins via transient gene expression: infiltration with a needleless syringe is a common method for laboratory studies [ 4 , 7 , 8 , 16 , 29 , 48 ], whereas vacuum infiltration is used for large commercial facilities (Medicago, Quebec, Canada; PlantForm, Toronto, Canada; Icon Genetics GmbH, Halle, Germany; Nomad Bioscience GmbH, Halle, Germany; [ 8 ]). Regardless, all plants must be agroinfiltrated.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that plant expression vectors, based on the backbones of plant self-replicating viruses, lead to high yields of recombinant protein, including proteins favorable for medicine uses [ 4 , 12 , 13 , 14 , 15 , 16 , 19 , 69 ]. As in this study, a PVX-based vector was used, it was not surprising that the high levels of reporter green fluorescent protein were detected in the individual upper leaves (up to 70–80% of the total soluble proteins).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation